The impact of additional visual tasks in physical exercise on balance ability among 9-10-year-old children: the mediating effect of visual acuity - Rongbin Yin; Guiming Zhu; Anqi Liu; Miyu Wang; Liangtao Li; Shengting Dai (Frontiers Media S.A., 2024)
PurposeThis study aimed to explore the effects of additional visual tasks in physical exercise on the vision and balance ability of children, and to verify whether children's vision mediated the influence of physical exercise on their balance ability.MethodsThe study randomly selected 86 students aged 9-10 years old from a school in Suzhou city, dividing them into an experimental group (n = 43) and a control group (n = 43). The experimental group participated in physical exercise with additional visual tasks, while the control group engaged in routine physical exercise. The experiment lasted for 16 weeks, with kinetic visual acuity (KVA), uncorrected distance visual acuity (UDVA), static balance, and dynamic balance measured before and after the experiment.ResultsThe results showed that after the experiment, the experimental group had significantly improved kinetic visual acuity (KVA), uncorrected distance visual acuity (UDVA), static balance, and dynamic balance. In contrast, the control group had significantly decreased kinetic visual acuity, no significant improvement in uncorrected distance visual acuity, and no significant difference in dynamic balance and static balance. In the experimental group, there was a moderate positive correlation between kinetic visual acuity and uncorrected distance visual acuity, and a moderate positive correlation between uncorrected distance visual acuity and both static and dynamic balance. The study also found that uncorrected distance visual acuity partially mediated the effect of additional visual tasks during physical exercise on static and dynamic balance among children.ConclusionIn conclusion, adding visual tasks to physical exercise had a positive effect on improving children's vision and balance ability. Kinetic visual acuity and uncorrected distance visual acuity were positively correlated, and uncorrected distance visual acuity was positively correlated with both static and dynamic balance. Uncorrected distance visual acuity partially mediated the effect of physical exercise on children's balance ability.